Assessing quality in software development: An agile methodology approach - Rodríguez-Hernández, V.; Espino-Gudiño, M.C.; González-Pérez, J.L.; Gudiño-Bazaldúa, J.; Castano, Victor (Journal of Advanced Computer Science & Technology, 2015)
A novel methodology, result of 10 years of in-field testing, which makes possible the convergence of different types of models and quality standards for Engineering and Computer Science Faculties, is presented. Since most software-developing companies are small and medium sized, the projects developed must focuson SCRUM and Extreme Programming (XP), opposed to a RUP, which is quite heavy, as well as on Personal Software Process (PSP) and Team Software Process (TSP), which provide students with competences and a structured framework. ISO 90003:2004 norm is employed to define the processes by means of a quality system without new requirements or changing the existing ones. Also, the model is based on ISO/IEC 25000 (ISO (IEC 9126 – ISO/IEC 14598)) to allow comparing software built by different metrics.